Subject‐Specific Multiscale Modeling to Investigate Effects of Transcranial Magnetic Stimulation. Issue 8 (8th May 2015) - Goodwin, Brian D.; Butson, Christopher R.
Abstract : Objective: Transcranial magnetic stimulation (TMS) is an effective intervention in noninvasive neuromodulation used to treat a number of neurophysiological disorders. Predicting the spatial extent to which neural tissue is affected by TMS remains a challenge. The goal of this study was to develop a computational model to predict specific locations of neural tissue that are activated during TMS. Using this approach, we assessed the effects of changing TMS coil orientation and waveform. Materials and Methods: We integrated novel techniques to develop a subject‐specific computational model, which contains three main components: 1) a figure‐8 coil (Magstim, Magstim Company Limited, Carmarthenshire, UK); 2) an electromagnetic, time‐dependent, nonhomogeneous, finite element model of the whole head; and 3) an adaptation of a previously published pyramidal cell neuron model. We then used our modeling approach to quantify the spatial extent of affected neural tissue for changes in TMS coil rotation and waveform. Results: We found that our model shows more detailed predictions than previously published models, which underestimate the spatial extent of neural activation. Our results suggest that fortuitous sites of neural activation occur for all tested coil orientations. Additionally, our model predictions show that excitability of individual neural elements changes with a coil rotation of ±15°. Conclusions: Our results indicate that the extent of neuromodulation is more widespread than previous published models suggest. Additionally, both specific locations in cortex and the extent of stimulation in cortex depend on coil orientation to within ±15° at a minimum. Lastly, through computational means, we are able to provide insight into the effects of TMS at a cellular level, which is currently unachievable by imaging modalities.